Engineering mechanics dynamics - Pytel, Andrew; Kiusalaas, Jaan (Cengage Learning, 2017)
This text is an unbound, binder-ready edition. Known for its accuracy, clarity, and dependability, Meriam & Kraige's Engineering Mechanics: Dynamics has provided a solid foundation of mechanics principles for more than 60 years. Now in its seventh edition, the text continues to help students develop their problem-solving skills with an extensive variety of engaging problems related to engineering design. More than 50% of the homework problems are new, and there are also a number of new sample problems. To help students build necessary visualization and problem-solving skills, the text strongly emphasizes drawing free-body diagrams-the most important skill needed to solve mechanics problems